Złocone ramy do obrazów. Konserwacja i restauracja w zarysie - Wantuch-Jarkiewicz, Katarzyna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
Conservation and restoration of gilt picture frames surfaces is not represented very much in the field literature. Is it so perhaps because of the natural continuation of gilding craft rather then conservation goals? Theoretical and practical bases of conservation and restoration of gilt picture frame surfaces were presented and disscuced. The subject of the discussion is old and worn gilt surfaces. They are worn and neither even in color nor in gloss. These and other matters one should take into account during and before restoring of old gilt surfaces. Both traditional and nontraditional methods were presented by the author.